Deaths of despair and the future of capitalism - Case, Anne. (Princeton Princeton University Press, 2021)
From economist Anne Case and Nobel Prize winner Angus Deaton, a groundbreaking account of how the flaws in capitalism are fatal for America's working class
Keywords: Suicide -- United States; Premature death -- United States; Public health -- United States; Life expectancy -- United States